Β Blockade after myocardial infarction: systematic review and meta regression analysis. Issue 7200 (26th June 1999) - Freemantle, Nick; Cleland, John; Young, Philip; Mason, James; Harrison, Jane
Abstract: Objectives : To assess the effectiveness of β blockers in short term treatment for acute myocardial infarction and in longer term secondary prevention; to examine predictive factors that may influence outcome and therefore choice of drug; and to examine the clinical importance of the results in the light of current treatment. Design :Systematic review of randomised controlled trials. Setting : Randomised controlled trials. Subjects : Patients with acute or past myocardial infarction. Intervention : βBlockers compared with control. Main :outcome measures All cause mortality and non-fatal reinfarction. Results : Overall, 5477 of 54 234 patients (10.1%) randomised to β blockers or control died. We identified a 23% reduction in the odds of death in long term trials (95% confidence interval 15% to 31%), but only a 4% reduction in the odds of death in short term trials (−8% to 15%). Meta regression in long term trials did not identify a significant reduction in effectiveness in drugs with cardioselectivity but did identify a near significant trend towards decreased benefit in drugs with intrinsic sympathomimetic activity. Most evidence is available for propranolol, timolol, and metoprolol. In long term trials, the number needed to treat for 2 years to avoid a death is 42, which compares favourably with other treatments for patients with acute or past myocardial infarction. Conclusions : β Blockers are effective in long term secondary prevention after myocardial infarction, but they are underused in such cases and lead to avoidable mortality and morbidity.